MEGALIT DAN KUBUR TEMPAYAN DATARAN TINGGI JAMBI DALAM PANDANGAN ARKEOLOGI DAN ETNOSEJARAH - Budisantosa, Tri Marhaeni Sosiana (Berkala Arkeologi, 2024)
One aspect of archaeological studies in highland of Jambi is ideology or belief existing within human mind. The ideology of the past society is not appeared directly through material culture. The ideological research, therefore, could approach closer to cultural system of the past with the supported by the endorsement of historical and ethnographical data of local community. This writing discusses development of such model to disclose the beliefs that playing a part in the construction of megaliths and burial jars in highland of Jambi. The problem is answered by relate the results of the discussion of archaeological data and ehtnohistorical data. Results of the discussion revealed that the archaeological data interpretation is supported by the etnhohistorical data.